Online Restaurant Reservation Application In The Region Of Sidoarjo Based On Android - Winda Hariyati; Mohammad Suryawinata (Procedia of Engineering and Life Science, 2021)
In sidoarjo area today is very much popping up restaurant business from large to small scale with various types of restaurants. Including restaurant sawung rasa and serba sambal that often apply reservations to the restaurant. With the number of customers making reservations, especially during the fasting month of course restaurants often experience overwhelmed and customers also often experience reservation rejections when visiting the restaurant because the restaurant is full of reservations. So it is necessary to have an online restaurant reservation application by utilizing technology into the process of reservation activities to provide new innovations. The design of this restaurant's online reservation application uses waterfall method. By implementing the results of the study using java programming language and firebase database as data storage. Therefore, the online reservation application of restaurants, especially sidoarjo area customers can easily and quickly make reservations with the value obtained from testing functionality on all features shows a percentage of 100% and by applying a likert scale poll for UAT results get a result of 84%.